Further tests of the HYPROP evaporation method for estimating the unsaturated soil hydraulic properties - Bezerra-Coelho Camila R.; Zhuang Luwen; Barbosa Maria C.; Soto Miguel Alfaro; van Genuchten Martinus Th. (Journal of Hydrology and Hydromechanics, 2018)
Many soil, hydrologic and environmental applications require information about the unsaturated soil hydraulic properties. The evaporation method has long been used for estimating the drying branches of the soil hydraulic functions. An increasingly popular version of the evaporation method is the semi-automated HYPROP© measurement system (HMS) commercialized by Decagon Devices (Pullman, WA) and UMS AG (München, Germany). Several studies were previously carried out to test the HMS methodology by using the Richards equation and the van-Genuchten-Mualem (VG) or Kosugi-Mualem soil hydraulic functions to obtain synthetic data for use in the HMS analysis, and then to compare results against the original hydraulic properties. Using HYDRUS-1D, we carried out independent tests of the HYPROP system as applied to the VG functions for a broad range of soil textures. Our results closely agreed with previous findings. Accurate estimates were especially obtained for the soil water retention curve and its parameters, at least over the range of available retention measurements. We also successfully tested a dual-porosity soil, as well as an extremely coarse medium with a very high van Genuchten n value. The latter case gave excellent results for water retention, but failed for the hydraulic conductivity. In many cases, especially for soils with intermediate and high n values, an independent estimate of the saturated hydraulic conductivity should be obtained. Overall, the HMS methodology performed extremely well and as such constitutes a much-needed addition to current soil hydraulic measurement techniques.